Criminal justice and crime in late Renaissance Florence, 1537-1609 / John K. Brackett. - Brackett, John K. (Cambridge University Press, 1992)
This book examines in detail the Florentine system of criminal justice under the reign of the first three Medici grand dukes, from 1537 to 1609. The author discusses the structure and functions of the court, the operation of the two city prisons, and the definition and treatment of the major categories of crime. His main purpose is to shed light on the character of the Medicean state by examining the effectiveness of its main instrument of social control. The study is important for the amount of detail that it offers for such an early period, and it helps to vitiate the usefulness of the term 'absolutist,' which conveys a misleading picture of the early modern state.